Carbon monoxide releasing molecule-3 alleviates neuron death after spinal cord injury via inflammasome regulationResearch in context - Gang Zheng; Yu Zhan; Haoli Wang; Zucheng Luo; Fanghong Zheng; Yifei Zhou; Yaosen Wu; Sheng Wang; Yan Wu; Guangheng Xiang; Cong Xu; Huazi Xu; et al. (EBioMedicine, 2019)
Background: Genetic overexpression or pharmacological activation of heme oxygenase (HO) are identified as potential therapeutic target for spinal cord injury (SCI); however, the role of carbon monoxide (CO), which is a major product of haem degenerated by HO, in SCI remains unknown. Applying hemin or chemicals which may regulate HO expression or activity to increase CO production are inadequate to elaborate the direct role of CO. Here, we assessed the effect of CO releasing molecule-3 (CORM-3), the classical donor of CO, in SCI and explained its possible protective mechanism. Methods: Rat SCI model was performed with a vascular clip (30 g) compressing at T9 vertebral level for 1 min and CO was delivered immediately after SCI by CORM-3. The neurological deficits and neuron survival were assessed. Inflammasome and inositol-requiring enzyme 1 (IRE1) pathway were measured by western blot and immunofluorescence. For in vitro study, oxygen glucose deprivation (OGD) simulated the SCI-inflammasome change in cultured the primary neurons. Findings: CORM-3 suppressed inflammasome signaling and pyroptosis occurrence, which consequently alleviated neuron death and improved motor functional recovery following SCI. As a pivotal sensor involving in endoplasmic reticulum stress-medicated inflammasome signaling, IRE1 and its downstream X-box binding protein 1 (XBP1) were activated in SCI tissues as well as in OGD neurons; while inhibition of IRE1 by STF-083010 in SCI rats or by si-RNA in OGD neurons suppressed inflammasome signaling and pyroptosis. Interestingly, the SCI/OGD-stimulated IRE1 activation was attenuated by CORM-3 treatment. Interpretations: CO may alleviate neuron death and improve motor functional recovery in SCI through IRE1 regulation, and administration of CO could be a promising therapeutic strategy for SCI. Keywords: Spinal cord injury, Neuron death, Inflammasome, Carbon monoxide